(untitled) (XXI Century. Spanish Literature and Culture, 2012)
The marriage which Ovejero mentions in this essay took place between reality and literature in the very origins of mankind. Aristotle himself was keenly aware of this marriage and of the many problems it posed. Tasso and then, later on, the romantics, the naturalists and indeed the realists themselves have been aware that it is an almost impossible task to separate reality from subjectivity. As Ovejero points out, this conundrum leads to a greater concern with the text itself, regardless of the writer or the reality it refers to. The text must be coherent in itself, and even if it refers to a historical event, it must be built within its own framework. A historical novel may mirror real events but it is the coherency of its own framework which will mark the success -or failure- of the novel as a work of art.